From the Body Image to the Body Schema, From the Proximal to the Distal: Embodied Musical Activity Toward Learning Instrumental Musical Skills - Kim, Jin Hyun (Frontiers in Psychology, 2020)
A recent paradigm shift in music research has allowed scholars to examine the macro- and micro-processes taking place within musical performance and underlying cognitive processes. Tying in with phenomenological theories of embodied perception and cognition, this paper focuses on bodily musical activity relevant to the acquisition of instrumental musical skills—the process of learning music. Dynamic interaction with musical instruments, accompanied by the interplay of action and passion, involves body image and body schema, whose status oscillates in different phases of the acquisition of instrumental musical skills; this interaction allows humans to direct attention from their bodily states—the proximal—to the quality of musical sounds and a unity of musical experience—the distal. It is thus argued that shaping music by means of playing a musical instrument can be conceived of as an embodied process, of understanding the forms of one’s own experience as related to the musical world that is created by one’s bodily activity.